Orchid diversity in a logging concession in Tabalong District, South Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Puspitaningtyas DM. 2020. Orchid diversity in a logging concession in Tabalong District, South Kalimantan, Indonesia. Biodiversitas 21: 5455-5464. Borneo is the third largest island in the world, and considered the "island of orchids" since it has approximately 2.500-3.000 species of orchids, equivalent to 10% of the orchids in the world. The aim of the research was to study orchid diversity in a logging concession in the village of Dambung Raya, Ara Bintang Sub-district, Tabalong District, South Kalimantan Province, Indonesia. This research also collected living specimens of orchid to be grown in Bogor Botanic Gardens, West Java, Indonesia, and Banua Botanic Gardens, Banjarbaru, South Kalimantan, Indonesia. The orchid inventory was carried out using explorative method. The study recorded 64 species of epiphyte orchids and one species of terrestrial orchid, altogether belong to 27 genera. Some interesting orchid species found in this area included Grammatophyllum speciosum Blume, Coelogyne spp. (C. motleyi Rolfe ex J.J.Wood, D.A.Clayton & C.L.Chan, C. foerstermannii Rchb.f., C. rochussenii de Vriese, C. pandurata Lindl.), Acriopsis spp., Pteroceras teres (Blume) Holttum, Thrixspermum raciborskii J.J.Sm. subsp. brevipollinium P. O'Byrne & A. Ent., Thecostele alata (Roxb.) EC Parish & Rchb.f., and Liparis pallida (Blume) Lindl. Orchid endemic to Borneo found in this area were Coelogyne motleyi Rolfe ex JJ Wood, DA Clayton & CL Chan, and Cleisostoma brachystachys (Ridl.) Garay.
Keywords: inventory, orchid, South Kalimantan, Tabalong Regency